(untitled) (Aporte Santiaguino, 2024)
The purpose was to study the environmental perception of users, authorities, representatives of the people and directors of institutions on the level of contamination, quality and quantity of surface water in the area of ​​direct influence of the Pierina mining company, after almost two decades since it began. its operations. The research is descriptive, non-experimental in design. The survey technique was applied to a sample of 182 water users, ten managers were interviewed and direct observation techniques were used. The results indicate that the contamination level is high/medium for 61.0% and 35.7%, respectively. The water has poor/fair quality, both in its physical (43.4% and 53.3%) and chemical characteristics (59.3% and 40.1%), respectively. During the dry months there is no water availability, the flow in the streams and springs is little/nothing (70.9% and 4.4% respectively). In conclusion, the majority of users perceive that before the arrival of the mining company, the quality of the water was good and in sufficient quantity, but this situation has gradually changed and currently the water is contaminated, is of poor quality and there is small amount, which affects the ecosystem as a whole.